Pengaruh Metode Pembelajaran Snowball Throwing Terhadap Kemampuan Berfikir Kreatif Siswa Pada Materi Virus Kelas X SMA Negeri 1 Luwuk - Hasjim, Yuli Karmila; Nurlia, Nurlia; Anggo, Sulasmi (Jurnal Biologi Babasal, 2022)
Abstract: The application of learning methods must be suitable to students' needs, in order to understand the material, encourage creative thinking, and focus on the task at hand.  This research aims to determine the influence of the  Snowball Throwing learning method on students' creative thinking ability on the Virus material class X SMA Negeri 1 Luwuk.  The type of research used is a pseudo-experiment (Quasi Experiment).  This research was carried out in the odd semester of the 2022  /2023  school year, to be precise in August 2022. The research design used is the Nonequivalent Control Group Design.  The population of this research was all students of class X MIPA at SMA Negeri 1 Luwuk for the  2022/2023 school year. The samples from this research were class XA which amounted to 27 students and class XE which amounted to 27 students. So, the total sample of this study was 54 students.  The data collection technique used 10  essay questions. The data were analyzed using a t-test to determine the effect of the Snowball Throwing method on students' creative thinking abilities. The results showed that there was no influence of the Snowball Throwing learning method on students' creative thinking ability in class X SMA Negeri 1 Luwuk virus material with a tcount = 0.835, and ttable value = 1.675 so tcount > ttable with significance level 0.407 > 0.05.